Identification and forecasting of coastal erosion using aerial and UAV images - Themistocleous, Kyriacos (My University, 2023)
This study seeks to establish a methodology in order to determine the rate of coastal erosion using temporal aerial and UAV images. Part of the methodology focuses on forecasting coastal erosion and mapping Posidonia oceanica. Initial results indicate that there may be a correlation between coastal erosion and other related dynamics, such as the presence of Posidonia oceanica. UAV images acquired using UAVS in the Spyros Beach area near Larnaca, Cyprus were compared with aerial photos provided by the Lands and Surveys Department of the Government of Cyprus in order to estimate coastal erosion. In this study, the results indicate that, instead of coastline erosion, the coastline is actually expanding at a constant rate over the forecasted period. The beach nourishment observed may be related to the reduction of Posidonia oceanica. This reduction of the Posidonia oceanica forms a natural breaker between the shoreline and the sea, leading to a reduction of wave energy which thereby results in an enhanced accumulation of sand at the beach.
Keywords: Unmanned aerial vehicles; Sand; Photogrammetry; Cameras; Image segmentation; Image processing; Point clouds; RGB color model; Coastal modeling